2022
DOI: 10.1021/acs.joc.1c02565
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Mediated C(sp2)–H Selenylation of Amino Pyrazole and Amino Uracils in the Presence of Rose Bengal as an Organophotocatalyst

Abstract: Herein, we report an efficient methodology for the synthesis of alkyl, benzyl, and phenyl selenoethers of aminopyrazoles and aminouracils by C­(sp2)–H functionalization in the presence of visible light and Rose Bengal as an organophotocatalyst. The reaction of amino pyrazole/iosothiazole/isoxazole or amino uracils with 0.5 equivalent of diphenyl/dibenzyl/diethyl diselenides in the presence of visible light in acetonitrile medium and a catalytic amount of Rose Bengal provided the corresponding phenyl, benzyl, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…After the one-pot condition (Scheme ) in our hand for the synthesis of 22a , different pyrazole amine 17 , , thiophenol 18 , and acetylene derivatives 19 were considered to explore the thiolation/[4 + 2] benzannulation reaction. As displayed in Scheme , we have identified that electron-donating substituents −Me and −OMe at the para position on 1-phenyl of pyrazole amine ( 17g and 17h ) afforded pleasing yields (61 and 63%) of the pyrazoloquinoline thioether compound ( 22g and 22h ) compared to halogen and electron-withdrawing substituents −Br ( 17b ), −Cl ( 17c ), −F ( 17d ), −CN ( 17e ), and −NO 2 ( 17f ), where the relative products ( 22b–22f ) were acquired in 46–56% yields, respectively (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the one-pot condition (Scheme ) in our hand for the synthesis of 22a , different pyrazole amine 17 , , thiophenol 18 , and acetylene derivatives 19 were considered to explore the thiolation/[4 + 2] benzannulation reaction. As displayed in Scheme , we have identified that electron-donating substituents −Me and −OMe at the para position on 1-phenyl of pyrazole amine ( 17g and 17h ) afforded pleasing yields (61 and 63%) of the pyrazoloquinoline thioether compound ( 22g and 22h ) compared to halogen and electron-withdrawing substituents −Br ( 17b ), −Cl ( 17c ), −F ( 17d ), −CN ( 17e ), and −NO 2 ( 17f ), where the relative products ( 22b–22f ) were acquired in 46–56% yields, respectively (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…The general procedure for the synthesis of compounds 17 : 3-phenyl pyrazole amine, 4-phenyl pyrazole amine, and pyrazole amine derivatives are synthesized according to the literature report. , Compounds 18 and 19 are commercially available.…”
Section: Methodsmentioning
confidence: 99%
“…The dried crude reaction mass was subjected to column chromatography to provide the corresponding pyrazole amine 7a in a good yield. The general procedure was followed for the preparation of all other pyrazole amine compounds 7b–7m . , …”
Section: Methodsmentioning
confidence: 99%
“…In 2022, Choudhury et al [ 47 ] reported a visible-light-mediated C(sp 2 )−H selenation reaction of aminopyrazoles ( Scheme 17 ). The authors chose 5-amino-3-methyl-1 H -phenylpyrazoles 83 and diphenyl diselenides as model substrates and demonstrated experimentally that the reaction does not require additional metal oxidants; only 12 h of visible-light irradiation in nitrogen at room temperature is required to obtain the desired target products.…”
Section: Application Of Dichalcogenides Under Visible-light Irradiationmentioning
confidence: 99%